x²-x+√(x²-2x-+6)=x+6

0 голосов
71 просмотров

x²-x+√(x²-2x-+6)=x+6


Алгебра (40 баллов) | 71 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

x^2-x+\sqrt{(x^2-2x+6)}=x+6
\sqrt{x^2-2x+6}=-x^2+2x+6 \\ x^2-2x+6=(-x^2+2x+6)^2 \\ x^2-2x+6=x^4-4x^3-8x^2+24x+36 \\ -x^4+4x^3+9x^2-26x-30=0 \\ -(x-3)(x+1)(x^2-2x-10)=0
(x-3)(x+1)(x^2-2x-10)=0 \\ x-3=0; x+1=0; x^2-2x-10=0 \\ x=3; x=-1; x^2-2x=10 \\ x=3;x=-1; x^2-2x+1=11 \\ x=3;x=-1; (x-1)^2=11 \\ x=3;x=-1; x-1=\sqrt{11};x-1=-\sqrt{11} \\ x=3;x=-1; x=1+\sqrt{11};x=1-\sqrt{11}

Ответ:x=3;x=-1

(2.2k баллов)
0 голосов

x²-x+√(x²-2x+6)=x+6

sqrt(x^2-2x+6)=x+6+x-x^2

sqrt(x^2-2x+6)=2x+6-x^2

sqrt(x^2-2x+6)=-x^2+2x+6

 sqrt(x^2-2x+6)=-(x^2-2x-6)

t=x^2-2x

sqrt(t+6)=-t+6

откуда t=3

x^2-2x=3

x^2-2x-3=0

x=-1, x=3

 

ответ: х=-1, х=3

(8.6k баллов)